# KERALA ENGINEERING / MEDICAL ENTRANCE EXAMINATIONS

KEAM 2014
Solutions

For All Answer Keys and Solutions
visit

SOLUTIONS & ANSWERS FOR KERALA ENGINEERING
ENTRANCE EXAMINATION - 2014 – PAPER II
VERSION – B1

[MATHEMATICS]

1. Ans: 185

Sol: 2 ⊕ 3 = 4 + 9 = 13
(2 ⊕ 3) ⊕ 4 = 13 ⊕ 4 = 13
2
+ 4
2

= 169 + 16
= 185.

2. Ans: 520

Sol:

30 = ( ) 30 x
100
10
+
⇒ x = 270 and
30 = ( ) y 30
100
12
+
⇒ y = 220
x + y + 30 = 270 + 220 + 30
= 520.

3. Ans: f is not a 1 − 1function

Sol: f(x) = |x − 2|
f(1) = |1 − 2| = 1
f(3) = |3 − 2| = 1
Not one-one.

4. Ans: 1680

Sol: 8P4 =
! 4
! 8

Sol: No correct option is given. Options (A) and
(D) are same. If one of them were [1, ∞),
that would have been the correct option.

6. Ans:

Sol: (fοg) (x) = 3 x 2 −
If the question were domain of (fοg) (x) is,
then (E) would be the correct option.
.

7. Ans: 2

Sol:
( ) ( )
( )
2
2
3
i 6 8
4 i 3 i 3
+
+ +

( )( )
36 i 96 64
16 i 24 9 i 3 3 i 9 3 3
− +
+ + − − − +
=
=
( )( )
2 2
96 28
i 96 28 192 i 56
i 96 28
192 i 56
+
− −
=
+

=
9216 784
i 18432 5376 5376 i 1568
+
+ − +

= i 2
10000
i 20000
=
∴ |z| = 2 2
2
= .

8. Ans: Re(z) = 0

Sol: Let ω = u + iv
∴ z =
1 iv u
1 iv u
1
1
+ +
− +
=
+ ω
− ω

=
( )
( )
( ) [ ] ( ) [ ]
( ) [ ] ( ) [ ] iv 1 u iv 1 u
iv 1 u iv 1 u
iv 1 u
iv 1 u
− + + +
− + + −
=
+ +
+ −

=
( ) ( )
2 2
2 2 2
v 1 u 2 u
v 1 u iv 1 u iv 1 u
+ + +
+ + + − − −

=
1 u 2 v u
iv iv 1 v u
2 2
2 2
+ + +
+ + − +

u 2 2
iv 2 0
+
+
=
|
¹
|

\
|
= + 1 v u
2 2
Q
=
u 1
iv
+
.

9. Ans:
3
i
e 3
π

Sol:
3
i 2
e
π
= cos ω =
π
+
π
3
2
sin i
3
2

∴ 1 + z + 3z
2
+ 2z
3
+ 2z
4
+ 3z
5

= 1 + ω + 3ω
2
+ 2ω
3
+ 2ω
4
+ 3ω
5

= 1 + ω + 3ω
2
+ 2 + 2ω + 3ω
2

= 3 + 3ω + 6ω
2
= 3(−1 + ω + ω
2
) + 3ω
2

= 3ω
2
= 3
3
i 4
e
π

C
y 30 x
M
w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

= |
¹
|

\
| π
+
π
3
4
sin i
3
4
cos 3
=
|
|
¹
|

\
|
|
¹
|

\
| π
+ π + |
¹
|

\
| π
+ π
3
sin i
3
cos 3
=
3
i
e 3
3
sin i
3
cos 3
π
− = |
¹
|

\
| π

π
− .

10. Ans: −128i

Sol: z1 = 2 2 (1 + i), z2 = 1 + 3 i
∴z1
2
= 4 × 2 (1 + i)
2

= 8(1 + 2i − 1)
= 16i
z2
3
= ( )
3
i 3 1+
= ( )
3
i 3 3 3 3 3 i 3 1 + × − +
= 1 + i 3 3 i 9 3 3 − −
= −8
∴ z1
2
z2
3
= 16i × −8 = −128 i.

11. Ans: 0

Sol: (z3 − z1) = (z2 − z1) [cos90 + isin 90]
(z3 − z1) = i(z2 − z1)
(z3 − z1)
2
= −(z2 − z1)
2

⇒ (z3 − z1)
2
+ (z2 − z1)
2
= 0.

12. Ans: a
2
− 4b = 4

Sol: Let α, α + 2 be two consecutive odd root
∴ α + α + 2 = a and α(α + 2) = b
∴ 2α + 2 = a
∴ α =
2
2 a −
and α
2
+ 2zα = b
since α
2
+ 2α = b

( )
b
2
2 a
2
4
2 a
2
= |
¹
|

\
| −
+

⇒ b 2 a
4
4 a 4 a
2
= − +
+ −

⇒ a
2
− 4a + 4 + 4a − 8 = 4b

⇒ a
2
− 4b = 4.

13. Ans: a
2
− 2b
2

Sol: α + β = a, αβ = b
2

α
2
+ β
2
= (α + β)
2
− 2αβ
= a
2
− 2b
2
.

14. Ans:
4
3

Sol: α + β = −3
αβ = −4

4
3
4
3 1 1
=

=
αβ
β + α
=
β
+
α
.

15. Ans: 2

Sol: ( ) 0 81 3 2 3
2 x x 2
= + −
+

⇒ 0 81 3 . 3 . 2 3
2 x x 2
= + −
⇒ 0 81 3 18 3
x x 2
= + −
⇒ ( ) 0 81 3 18 3
x
2
x
= + −
⇒ (3
x
− 9)
2
= 0
⇒ 3
x
− 9 = 0
⇒ 3
x
= 3
2

⇒ x = 2.

16. Ans:
( )
4
2
β − α

Sol: α + β = −2b ⇒ b =
2 −
β + α

αβ = c
∴ b
2
− c = αβ − |
¹
|

\
|

β + α
2
2

=
( ) ( )
4 4
4
2 2
β − α
=
αβ − β + α

17. Ans: 4x
2
− 5x + 1 = 0

Sol: 2x
2
+ 3x + 1 = 0
α + β =
2
3 −
, αβ =
2
1

∴ α
2
+ β
2
= ( ) αβ − β + α 2
2

=
2
1
2
2
3
2
× − |
¹
|

\
| −

=
4
5
1
4
9
= −
0
4
1
x
4
5
x
2
= + − .

18. Ans:
20
1

Sol:
( )( ) ( )( )
∑ ∑
= =
+ +

=
+ +
17
8 n
17
8 n
3 n 2 n
2 3
3 n 2 n
1

=
( ) ( )
( )( )

=
+ +
+ − +
17
8 n
3 n 2 n
2 n 3 n

=

=
(
¸
(

¸

+

+
17
8 n
3 n
1
2 n
1

= ....
12
1
11
1
11
1
10
1
+ |
¹
|

\
|
− + |
¹
|

\
|

….. |
¹
|

\
|
− +
20
1
19
1

=
20
1
20
1 2
20
1
10
1
=

= −

w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

19. Ans: 3 : 1

Sol: a : b = 3 +
2
2 : 3 −
2
2
3
2
6
2
b a
= =
+

1 1 ab = =

1
3
M . G
M . A
= ⇒ A.M : G.M = 3 : 1.

20. Ans: 1020

Sol: x1 + x4 + x9 + x11 + x20 + x22 +
x27 + x30 = 272
⇒ a + a + 3d + a + 8d + a + 10d +
a + 19d + a + 21d + a + 26d + a + 29d
= 272
⇒ 8a + 116d = 272 ⇒ 4(2a + 29d) = 272
x1 + x2 + ……. + x30 = S30 = [ ] d 29 a 2
2
30
+
= 15 ×
4
272

= 1020.

21. Ans:
2
189

Sol: ar = 24, ar
4
= 3

24
3
ar
ar
4
= ⇒ r
3
=
8
1
⇒ r =
2
1

∴ a + ar + ar
2
+ ar
3
+ ar
4
+ ar
5

= a (1 + r + r
2
+ r
3
+ r
4
+ r
5
)
= 48
|
|
¹
|

\
|
+ + + +
5 2
2
1
......
2
1
2
1
1
= 48
2
189
2
1
2
1
1 48
2
1
1
2
1
1
6
6
=
|
|
¹
|

\
|

=

|
|
¹
|

\
|
|
¹
|

\
|

.

22. Ans: 35

Sol: [ ] d 74 a 2
2
75
+ = 2625
75[a + 37d] = 2625
a + 37d = 35
75
2625
= .

23. Ans: −3

Sol: 2k = −6
k = −3.

24. Ans: 9

Sol: Tn =
n
C3
Tn + 1 − Tn =
(n + 1)
C3 −
n
C3
=
n
C2 = 36

( )
36
2 . 1
1 n n
=

⇒ n(n − 1) = 72
⇒ n
2
− n − 72 = 0
⇒ (n − 9) (n + 8) = 0
⇒ n = 9.

25. Ans:
10
C5

Sol: Tr + 1 =
10
Cr
r r 10
10
x
x
10
|
¹
|

\
|
|
¹
|

\
|

T5 + 1 =
5 5 10
5
10
10
x
x
10
C |
¹
|

\
|
|
¹
|

\
|

=
5 5
5
10
10
x
x
10
C |
¹
|

\
|
|
¹
|

\
|

=
10
C5.

26. Ans: −1275

Sol: x
49
(−1 − 2 −3 − ……. − 50)
= −x
49
(1 + 2 + 3 + …… + 50)
= −x
49
|
¹
|

\
| ×
2
51 50

= −1275 x
49
.

27. Ans: 729

Sol: Put x = 1
Then ( )
6 6
6
3 2 1 x 2
x
1
= + = |
¹
|

\
|
+
= 729.

28. Ans:
2
2 n n
2
− +

Sol: 2P1 + 3P1 + …… + nP1
= 2 + 3 + …… + n
=
( )
1
2
1 n n

+

=
2
2 n n
2
− +
.

29. Ans: 400

Sol: a can take the values 1, 3, 5, 7, 9
b can take 0, 3, 6, 9
c can take 0, 2, 4, 6, 8
d can take 2, 3, 5, 7
∴ Total number of 4 digit numbers
= 5C1 × 4C1 × 5C1 × 4C1
= 5 × 4 × 5 × 4
= 400.

30. Ans: 0

Sol:
0 a a a a
0 a a a a
1 a a
1 a a
1 a a
1 a a
3 4 2 3
2 3 1 2
2 1
4 3
3 2
2 1
− −
− − =
R2 → R2 − R1
R3 → R3 − R2
w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

= 0
0 d d
0 d d
1 a a
2 1
= .

31. Ans:
8
1

Sol: Area of the triangle
1
c
y
c
x
1
b
y
b
x
1
b
y
a
x
2
1
3 3
2 2
1 1

=
c y x
b y x
a y x
abc 2
1
3 3
2 2
1 1

c 2 y x
b 2 y x
a 2 y x
abc
1
4
1
3 3
2 2
1 1
= C3 → 2C3
=
8
1
2
abc
abc
1
4
1
= × × .

32. Ans: a ≠ 2

Sol: 3x + y − z = 2
x + 0 y − z = 1
2x + 2y + a = 5
0
a 2 2
1 0 1
1 1 3
≠ −

⇒ 3(0 + 2) −1(a + 2) − 1(2 − 0) ≠ 0
⇒ 6 − a − 2 − 2 ≠ 0
⇒ 2 − a ≠ 0
⇒ a ≠ 2.

33. Ans: 4

Sol: 0
k 3 1
2 k 2
=

(since matrix is singular)
⇒ (2 − k) (3 − k) − 2 = 0
⇒ 6 − 5k + k
2
− 2 = 0
⇒ k
2
− 5k + 4 = 0
⇒ −k
2
+ 5k − 4 = 0
⇒ 5k − k
2
= 4.

34. Ans: zero

Sol:
1 log c log
c
1
log
c
1
log 1 log
b
1
log
c log b log 1 log
c a a
a b a
a a a
|
¹
|

\
|
|
¹
|

\
|
|
¹
|

\
|

=
1 log c log c log
c log 1 log b log
c log b log 1 log

− −
= , 0
0 c log c log
c log 0 b log
c log b log 0
=

− − because
the determinant of a skew symmetric
matrix of odd order is zero.

35. Ans: 1

Sol: 2x + y − 4 = 0
3x + 2y − 2 = 0
x + y + 2 = 0
( ) ( ) ( ) 2 3 4 2 6 2 4 2
2 1 1
2 2 3
4 1 2
− − + − + = −

= 12 − 8 − 4 = 0
∴ The system of equation has a unique
solution.

36. Ans: 0

Sol:

37. Ans: 14x + 5y ≥ 70, y ≤ 14 and x − y ≥ 5

38. Ans: ~[p ∨ (~q)] ≡ (~p) ∧ q

39. Ans: F, F, T

40. Ans: p ∨ (~q)

Sol: ~ [(~p) ∧ q] = ~(~p) ∨ ~q
= p ∨ ~q.

41. Ans: sinθ + cosθ ≤ 2

Sol: a sinθ + b cosθ ≤
2 2
b a +
⇒ sinθ + cosθ ≤
2 2
1 1 +
≤ 2

42. Ans:
2
π

Sol:

2 2
3
1
2 2
3
1
−2 2
0
f(x) = −2x + 2
f(x) = 2x
4
w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

Given sum = ( )
|
|
¹
|

\
|
+
− −
2 2
1
tan 2 2 tan
1 1

= ( ) ( )
2
2 2 cot 2 2 tan
1 1
π
= +
− −
.

43. Ans:
ab 1
b a

+

Sol: Given sum = 2 tan
−1
a + 2 tan
−1
b
= 2 x tan 2
ab 1
b a
tan
1 1 − −
= |
¹
|

\
|

+

⇒ x =
ab 1
b a

+

44. Ans:
° 2 sin
2

Sol: Given sum = tan 1° + cot 1°
=
° °
° + °
1 cos . 1 sin
1 cos 1 sin
2 2

=
° ° 1 cos . 1 sin 2
2

=
° 2 sin
2
.

45. Ans: 0

Sol: S5 = 0
2
cos
10
5
cos =
π
=
π
.

46. Ans:
5

Sol: |
¹
|

\
| π
− π = |
¹
|

\
| π
− −
5
3
2 cos cos
5
7
cos cos
1 1

=
5
3
5
3
cos cos
1
π
=
π

.

47. Ans: 15

Sol: Given sum = 1 + tan
2
(tan
−1
3) +
1 + cot
2
( ) 2 cot
1 −

= 1 + 3
2
+ 1 + 2
2
= 15.

48. Ans: 2

Sol: sinθ + cosec θ = 2
⇒ sinθ = 1
∴ sin
6
θ + cosec
6
θ = 1
6
+ 1
6
= 2.

49. Ans: 2

Sol: ( ) [ ] x f Lt
0 x
+

(
(
(
(
¸
(

¸

+ +
+ + +
=
+

x
x 3 sin 12
x
x 5 sin 6
x
x 7 sin
x
x 2 sin 12
x
x 4 sin 18
x
x 6 sin 7
x
x 8 sin
Lt
0 x

= 2
Only option (D) matches.

50. Ans: –4

Sol:

M is |
¹
|

\
|
= |
¹
|

\
| + +
3 ,
2
7
2
1 5
,
2
5 2

Y = 2x + K passes through |
¹
|

\
|
3 ,
2
7

⇒ K = –4

51. Ans: (5, 2)

Sol:

Circum centre is the mid point of
Hypotenuse
⇒ |
¹
|

\
| + − +
2
6 2
,
2
8 2

⇒ (5, 2)

52. Ans: 1 :1

Sol: The required ratio is

( ) ( )
( ) ( )
|
|
¹
|

\
|
− − +
− + −
− =
|
|
¹
|

\
|
+ +
+ +

7 5 5 6 2
7 7 5 4 2
c by ax
c by ax
2 2
1 1

= 1 :1

53. Ans: 4

Sol: a
2
− b
2
= 512
⇒ (a + b) (a − b) = 2
9

⇒ (a + b, a − b) = (2
8
, 2), (2
7
, 2
2
), (2
6
, 2
3
),
(2
5
, 2
4
)
(Q a > b, a + b > a − b), the other
combinations like (2
4
, 2
5
) etc cannot be
accepted) 2
9
, 1 also cannot be accepted
since a and b are positive integers.
M
D
A
(2, 5)
B
C (5, 1)
R (8, 6)
Q (8, –2)
P
(2, –2)
C
w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

54. Ans:
5
1

Sol: The line is
( ) ( )
4
1
y
3
1
x
+ = 1
⇒ 3x + 4y − 1 = 0
P =
( ) ( )
2 2
4 3
1 0 4 0 3
+
− +
=
5
1
.

55. Ans:
2
7 −

Sol: Centre : (4, −1)
Given parabola is y = (x − 2)
2
+ 6
⇒ (x − 2)
2
= 4 . ( ) 6 y
4
1

∴ Vertex is (2, 6)
∴ slope =
2
7 −
.

56. Ans:
2
1

Sol: The required line is x − 2y + k = 0 passes
through (1, 1)
⇒ 1 − 2 + k = 0 ⇒ k = 1
∴ x − 2y + 1 = 0
y intercept =
2
1
2
1
b
c
=

=

.

57. Ans: a
2

Sol: p =
θ + θ

2 2
ec cos sec
a

θ θ
θ + θ
=
2 2
2 2
cos sin
cos sin
a

= asinθ cosθ = θ 2 sin
2
a

q = θ =
θ + θ
θ −
2 cos a
sin cos
2 cos a
2 2

∴ 4p
2
+ q
2
= a
2
(sin
2
2θ + cos
2
2θ) = a
2
.

58. Ans: 2

Sol: C1 : (1, −2), C2 (−2, 2)
r1 = 1 r2 = 2
C1 C2 =
2 1
r r 5 16 9 + > = +
∴ Two circles do not intersect
∴ dmin = C1 C2 − (r1 + r2)
= 5 − (1 + 2) = 2.

59. Ans: (9, 8)

Sol:

( ) 5 , 5
2
2 k
,
2
1 h
= |
¹
|

\
| + +

⇒ h= 9 and k = 8.

60. Ans: 2

Sol:

The two circles touch internally
⇒ C1C2 = |r1 − r2|

2 2
k h + =
2 2
k h 4 + −
⇒ 4 k h 2
2 2
= + ⇒ 2 k h
2 2
= +
∴ r = 2.

61. Ans: (x – 2)
2
+ (y – 2)
2
= 8

Sol: Let the required circle be
x
2
+ y
2
+ 2gx + 2fy + c = 0 ––––(1)
8 c f g
2 2
= − + ⇒ g
2
+ f
2
= 8 –––(2)
16 + 8g = 0 ⇒ g = –2
⇒ f
2
= 4 ⇒ f = –2
∴ Req uired circle is x
2
+ y
2
– 4x – 4y = 0
or (x – 2)
2
+ (y – 2)
2
= 8

62. Ans: x = cosθ – 1, y = 2sinθ + 1

Sol:
( ) ( )
1
2
1 y
1
1 x
2
2 2
=

+
+

⇒ x + 1 = 1 cosθ and y – 1 = 2sinθ
⇒ x = cosθ – 1 and y = 2sinθ + 1

63. Ans: 10

Sol:
5
3
e
PM
PF
= =
⇒ PM = 10 6
3
5
PF
3
5
= × = ×

64. Ans: 1
6
y
3
x
2 2
= −

(0, 1)
(h, K)
x
2
+ y
2
= 16
(0, 0)
(h, K) (1, 2)
5
5
w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

Sol: a 3 2 b 3 4
a
b 2
2
2
= ⇒ =
2a = 3 a 3 2 = ⇒
⇒ b
2
= 6 3 3 2 = ×
⇒ 1
6
y
3
x
2 2
= −

65. Ans:
5
24

Sol: Focus : (ae, 0) = |
¹
|

\
|
0 ,
4
a 5

2x + 3y − 6 = 0 passes through |
¹
|

\
|
0 ,
4
a 5

⇒ ( ) 0 6 0 3
4
a 5
2 = − + |
¹
|

\
|

⇒ 6
2
a 5
= ⇒ a =
5
12

∴ 2a =
5
24
.

66. Ans:

Sol: a = cosα
Given ellipse is 1
9
y
16
x
2 2
= +
Foci ⇒ ( ) ( ) 0 , 7 0 , 9 16 ± = − ±
⇒ a
2
+ b
2
= 7 ⇒ b
2
= 7 – cos
2
α
∴ 1
cos 7
y
cos
x
2
2
2
2
=
α −

α

67. Ans:
4
15

Sol: A = θ = × sin b . a
2
1
b a
2
1

=
4
15
2
1
5 4 4 1
2
1
= × × + +

68. Ans: a 3 b
r
r

Sol: cos6θ =
( )
a b a
a b a
r
r
r
r
r
r
• +
• +

=
a . b a
a
a b a
b . a a
2
2
r
r
r
r
r
r
r
r
r r
+
=
• +
+

=
b a
a
r
r
r
+
, where
2
2
2
b a b a
r
r
r
r
+ = +
∴ a 3 b
b a
a
2
1
2
2
r
r
r
r
r
= =
+
=

69. Ans:

Sol:

j
ˆ
k
ˆ
C A − =
r

i
ˆ
k
ˆ
AB − =
cosθ =
2
1
2 . 2
0 0 0 1
=
+ − −

⇒ θ = 60°
θ =
3
π

70. Ans: 7

Sol:
2
2
2
b b . a 2 a b a
r r
r r
r
r
+ − = −
⇒ 7 = 14 –2
2 2
b b
r r
+

2
b
r
= 7
⇒ 7 b =
r

71. Ans:
2
2
2
c b a
r
r
r
+ +

Sol: + + + = + +
2
2
2
2
c b a c b a
r
r
r r
r
r

[ ] c . b c . a b . a 2
r
r
r r r
+ + +
( ) 0 c b . a . e . i c b a = + + ⊥
r
r
r r
r
r
–––(1)
Similarly ( ) 0 a c . b = +
r r
r
––––(2)
& ( ) 0 b a . c = +
r
r r
–––––(3)
(1) + (2) + (3)
( ) 0 c . b c . a b . a 2 = + +
r
r
r r
r
r

2
2
2
2
c b a c b a
r
r
r r
r
r
+ + = + +

72. Ans: –25

Sol:
2 2 2 2
w v u w v u
r r r r r r
+ + + + +
[ ] w . u w . v v . u 2
r r r r r r
+ + + = 0
∴ 9 + 16 +25 = –2 [ ] w . u w . v v . u
r r r r r r
+ +
[ ] w . u w . v v . u
r r r r r r
+ + = 25
2
50
− =

73. Ans:
7
1
±

Sol: ( ) 1 k
ˆ
6 j
ˆ
2 i
ˆ
3 = − + λ
A B
C ( ) k
ˆ
i
ˆ
+
( ) k
ˆ
j
ˆ
+ ( ) j
ˆ
i
ˆ
+
w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

= ( ) 1 k
ˆ
6 j
ˆ
2 i
ˆ
3 = − + λ
⇒ 1 36 4 9 = + + λ
|λ| 49 =1

7
1
49
1
± = = λ

74. Ans: k
ˆ
2 j
ˆ
i
ˆ
2 + −

Sol: The required vector
= ( ) k
ˆ
n j
ˆ
m i
ˆ
3 + + l
where 1
9
4
9
a
9
4
2
= + +
⇒ a
2
= 1 ⇒ a = 1
∴ vector is |
¹
|

\
|
+ − k
ˆ
3
2
j
ˆ
3
1
i
ˆ
3
2
3
= k
ˆ
2 j
ˆ
i
ˆ
2 + −

75. Ans: ( ) k
ˆ
11 j
ˆ
3 i
ˆ
5 . r − +
r
=
2
135

Sol: Mid point of PQ is
|
¹
|

\
| −
2
9
,
2
7
,
2
3

DR of the normal is 5, 3, –11
∴ Plane is
0
2
9
z 11
2
7
y 3
2
3
x 5 = |
¹
|

\
|
+ − |
¹
|

\
|
− + |
¹
|

\
|

⇒ 5x + 3y – 11z =
2
135

⇒ ( ) k
ˆ
11 j
ˆ
3 i
ˆ
5 . r − +
r
=
2
135

76. Ans:
2
π

Sol: Ι
st
line is
2
5 z
2
3
2
3
y
1
1 x +
=
|
¹
|

\
|
+
=

2
nd
line is
0
2 z
2
1 y
3
2 x −
=

+
=

cosθ = 0 0 4 9
4
4
9
1
0 3 3
= + +
+ +
− −

θ = 90°
θ =
2
π

77. Ans:
3
1 z
4
3 y
5
2 x −
=

=

Sol: Let DR of the line of intersection of the
planes be a, b, c
⇒ a – 2b – c = 0 ––––(1)
a + b + 3c = 0 ––––(2)

3
c
4
b
5
a
= =

⇒ a = –5k, b = –4k, c= 3k

3
1 z
4
3 y
5
2 x −
=

=

78. Ans: ( ) k
ˆ
4 j
ˆ
i
ˆ
3
26
1
− −

Sol: DR of the line : 3, –1, –4
DC’ S :
26
4
,
26
1
,
26
3 − −

79. Ans: cos
–1
|
¹
|

\
|
3
2

Sol: DR’s of the normal : 2, −1, 2
DR’s of Z axis : 0, 0, 1
cosθ =
( )( ) ( ) ( )( ) ( )
3
2
1 0 0 4 1 4
1 2 0 1 0 2
=
+ + + +
+ − +

⇒ θ = cos
−1
|
¹
|

\
|
3
2
.

80. Ans: (2, –3, 4)

Sol:
c
z z
b
y y
a
x x
1 1 1

=

=

( )
2 2 2
1 1 1
c b a
cz by ax
+ +
+ + −
=
∴ 1
29
29
4
z
3
y
2
x
= = =

=
⇒ x = 2, y= –3, z = 4

81. Ans: 13

Sol: 13 25 144 = +

82. Ans: 2

Sol:
∑ ∑
= ⇒ = − 54 x 9 45 x
i i

= × + × − 45 9 25 54 10 x
2
i

= 360 x
2
i

⇒ σ = 2
9
54
9
360
2
= |
¹
|

\
|

83. Ans:
8
13

Sol: Events:
(1, 5), (1, 6), (2, 4), (2, 5), (2, 6)
(3, 3), (3, 4), (3, 5), (3, 6), (4, 2)
(4, 3), (4, 4), (4, 5), (4, 6), (5, 1)
(5, 2), (5, 3), (5, 4), (5, 5), (5, 6)
(6, 1), (6, 2), (6, 3), (6, 4), (6, 5), (6, 6)
w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

Probability =
8
13
6 6
26
=
×

84. Ans: [1 – P(A)] . P(B’)

Sol: P (A ∪ B)’ = P(A’ ∩ B’)
= P(A’) P(B’)
= [1 – P(A)] . P(B’)

85. Ans: 14

Sol: σ =
12
1 n
d
2

=
12
1 49
7

= 7 × 2 = 14

86. Ans:
216
5

Sol:
216
5
3 8
3 5
7
4
=
×
×

87. Ans: 5

Sol:
( ) ( )
( ) ( ) 1 x x 1 x
1 x 1 x
lim
2 2
3 5
1 x
+ − −
+ −

=
1 x
1 x
lim
5 5
1 x −

= 5 × 1
4
= 5

88. Ans:
5
3

Sol:
( )
5
3
x 5
x 5
1 e
x 3
x 3 x 3 1 log
lim
x 5
2
2
0 x
=
|
|
¹
|

\
|

× +

89. Ans: x

Sol:
1
1 x 3
6 x 3
2
1 x 3
2 x
1 x 3
2 x
f

+
+

+
= |
¹
|

\
|

+
= x

90. Ans: –1 and 2

Sol:
2 x
lim

ax + 3 =
2 x
lim

ax
2
– 1
⇒ 2a + 3 = 2a
2
– 1
⇒ 2a
2
= 2a – 4 = 0
⇒ a = –1, 2

91. Ans: f’(x) = 0

Sol: |f(x) – f(y)|
2
≤ |x – y|
3
–––(1)
|f(y) – f(x)|
2
≤ |y – x|
3
–––(2)
If x > y, 2
nd
inequality will be wrong
If x < y. 1
st
inequality will be wrong
So only possiblity is f(x) = k(a constant
function)
f’(x) = 0

92. Ans: 1

Sol: f(x) = ( )dt t cos 1
2
1
x
1

= [ ]
x
1
t sin t
2
1

= [ ] 1 sin 1 x sin x
2
1
+ − −
f’(x) = [ ] x cos 1
2
1

f’(π) = [ ] 1 1 1
2
1
= +

93. Ans: 10

Sol: ( ) x 2 2 x ' f
dx
dy
2
+ =

1 x
dx
dy
=
= 5 x 2 × 1
= 10

94. Ans: –4

Sol: f’(x) = 2x + b
10 + b = 2 × ( 7 + b) = 14 + 2b
b = –4

95. Ans:
t cos
1
3

Sol:
t cos
1
t cos
t sec
dx
dy
3
2
= =

96. Ans: θ
2
sec

Sol:
θ θ −
θ θ
=
sin cos a 3
cos sin a 3
dx
dy
2
2

= tanθ
θ = |
¹
|

\
|
+
2
2
sec
dx
dy
1

97. Ans:
2
x 1
2

Sol: x = sinθ ⇒ y = 2sin
–1
x

2
x 1
2
dx
dy

=

w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

98. Ans: (–1, 1)

Sol: 2y 4
dx
dy
= ⇒
y
2
dx
dy
=
1 y 2
y
2
= ⇒ =
⇒ 1 = 4x + 5
x = –1
(–1, 1)

99. Ans: x∈ (2, 3)

Sol: f’(x) = 6x
2
– 30x + 36
= 6(x
2
– 5x +6)
= 6(x – 2) (x – 3) < 0
x∈ (2, 3)

100. Ans: 15

Sol: y
2
e
xy

dx
dy
y 2 . e y
dx
dy
x
xy
+ |
¹
|

\
|
+ = 9e
–3
. 2x
9. e
–3

3 3
e 18
dx
dy
6 . e 3
dx
dy
− −
− = +
(
¸
(

¸

+

–9y1 + 27 + 6y1 = –18
–3y1 + 27 = –18
3y1 = 45
y1 = 15

101. Ans: –6

Sol: V = πr
2
h
0
dt
dr
r 2 . h
dt
dh
r
dt
dv
2
=
(
¸
(

¸

+ π =
⇒ ( ) 0 5 . 30
dt
dh
. 25 = +
6
25
150
dt
dh
− =

=

102. Ans: f(x) is not differentiable at x = 4

Sol: f(x) is not differentiable at x = 4

103. Ans:
4
1

Sol: y = x
2

2
x
1

3
x
2
x 2
dx
dy
+ = = −2 + −2 = −4

4
1
dx
dy
1

=
|
¹
|

\
|

=
4
1
.

104. Ans: 2 −

Sol: 2 1 1
2 2
− = + −

105. Ans:
( )
C
x
x 1
4
1
4
+
+

Sol:

|
|
¹
|

\
|
+
4
3
4
5
x
1
1 x
dx

1 +

− ⇒ =
4
3 4
t
dt
4
1
t
x
1

= C
4
1
t
4
1
4
1
+

= C
x
1
1
4
1
4
+
|
|
¹
|

\
|
+ −

( )
C
x
x 1
4
1
4
+
+

106. Ans: – cot (x e
x
) + C

Sol: x e
x
= t ⇒

dt ect cos
2
= – cot t + C
= – cot (x e
x
) + C

107. Ans: C
1 x
e
x
+
+

Sol:
( )
∫ |
|
¹
|

\
|
+

+
dx
x 1
1
x 1
1
e
2
x

= C
1 x
e
x
+
+

108. Ans: e
x
sin
2
x + C

Sol: ( )

+ dx x cos x sin 2 x sin e
2 x

= e
x
sin
2
x + C

109. Ans: 2 C
2
x
sin 2 +

Sol:

dx
2
x
cos 2
2

=

dx
2
x
cos 2
= C
2
1
2
x
sin
2 +
= C
2
x
sin 2 2 +

110. Ans: C x sec 1 x
1 2
+ − −

Sol: x = sec θ ⇒

θ
θ θ θ θ
sec
d tan sec tan

w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

= ( )

θ − θ d 1 sec
2

= tan θ - θ + C
= C x sec 1 x
1 2
+ − −

111. Ans: C
x
5
1
15
1
2
3
2
+
|
|
¹
|

\
|
+

Sol: x = 5 tan θ ⇒

+
dx
x
x 5
4
2

=

θ
θ θ θ
4
2
tan 25
d sec 5 sec 5

=

θ
θ
θ
d
sin
cos
5
1
4

=
∫ 4
t
dt
5
1

= C
t
1
15
1
3
+
cosec x =
2
2
x
5 x +

= C
x
5
1
15
1
2
3
2
+
|
|
¹
|

\
|
+

112. Ans: |
¹
|

\
| +
2
e 1
log
e
1

Sol:
( )
∫ ∫

+
=
+
1
0
e
1
x x
x
x
e e e
dx e
e 1
dx

e
x
= t
e
x
dx = dt

( )
∫ ∫
|
¹
|

\
|
+
− =
+
=
e
1
e
1
e t
1
t
1
e
1
e t t
dt

=
e
1
e t
t
log
e
1
(
¸
(

¸

|
¹
|

\
|
+

=
(
¸
(

¸

|
¹
|

\
|
+
− |
¹
|

\
|
e 1
1
log
e 2
e
log
e
1

=
( )(
(
(
¸
(

¸

+ e 1
1
2
1
log
e
1

= |
¹
|

\
| +
2
e 1
log
e
1

113. Ans: e + 2
e
1

Sol: e
x
= e
x
⇒ x = 0
A = ( )

1
0
x x
dx e e
= (e
x
– e
–x
) dx
= e + 2
e
1
− .

114. Ans:
2
1

Sol:

+
e
1
dx
x 3
x log 1

=

2
1
dt t
3
1

=
2
2
2
t
3
1
|
|
¹
|

\
|

= ( )
2
1
1 4
6
1
= −

115. Ans:
16
π

Sol:

+
⇒ =
1
0
8
3
4
x 1
dx x
t x
=

+
1
0
2
t 1
dt
4
1

= ( )
1
0
1
t tan
4
1

=
16 4 4
1 π
=
π
×

116. Ans: ( )
2
2 log
2
3

Sol:
∫ ∫
=
4
2
4 log
2 log
dx x
t
dt t log

=
4 log 2
2 log
2
2
x
|
|
¹
|

\
|

= ( ) ( ) [ ]
2 2
2 log 2 log 4
2
1

= ( )
2
2 log 3
2
1
×
= ( )
2
2 log
2
3

117. Ans: x
3
+ y
3
= 3 k xy + C

Sol: k [x dy + y dx]
= x
2
dx + y
2
dy
⇒ k [d (x y) = ( )
3 3
y x d
3
1
+
⇒ k x y = k
3
y x
3 3
+
+

⇒ x
3
+ y
3
= 3 k xy + C
= x
3
+ y
3
= 3 k xy + C
w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m

118. Ans: y = x + e
x
+ C

Sol: dy = e
x
+ 1) dx
y = e
x
+ x + C
y = x + e
x
+ C

119. Ans: 2, 2

Sol:
2
2 2
3
2
dx
y d
y
dx
y d
− =
|
|
¹
|

\
|

2
2
2
3
dx
y d
y
dx
dy
|
|
¹
|

\
|
− = |
¹
|

\
|

= 2, 2

120. Ans: sin
2
x

Sol: ( ) ecx cos y x cot 2
dx
dy
= +
I.F =

dx x cot 2
e
= x sin e
2 ) x log(sin 2
=

w
w
w
.
a
d
m
i
s
s
i
o
n
.
a
g
l
a
s
e
m
.
c
o
m